Enhancing quality education: Analyzing the comprehension levels of college freshmen students through their reading skills - Garcia, Cesar H.; Aquino, Rommel Dg. (Edelweiss Applied Science and Technology, 2025)
This study investigates the comprehension levels of college freshmen students to enhance the quality of education through improved reading skills. Using a descriptive quantitative design, it examined 143 first-year students enrolled in the Bachelor of Elementary Education (BEEd) and Bachelor of Secondary Education (BSEd) programs at the Eulogio “Amang” Rodriguez Institute of Science and Technology. A validated comprehension test assessed literal, interpretative, and critical reading skills. Results revealed that students performed best in literal comprehension, followed by interpretative and critical levels, indicating foundational proficiency but limited higher-order comprehension. A significant difference was found between BEEd and BSEd students in interpretative reading, favoring BEEd students. These findings underscore the need for instructional strategies that strengthen metacognitive awareness, critical literacy, and analytical reasoning. The study contributes to understanding literacy development and supports curriculum reforms aligned with the United Nations Sustainable Development Goal (SDG) 4: Quality Education.